Lithium battery diaphragm with high heat resistance and high liquid absorption and retention rate and preparation method of lithium battery diaphragm

By using porous aluminum oxide, ethyleneimine, silane coupling agent and polyvinyl alcohol in the lithium-ion battery separator, the shortcomings of existing lithium-ion battery separators in heat resistance, liquid absorption rate, etc. are solved, and the overall performance and safety performance of the battery are significantly improved.

CN119833877AActive Publication Date: 2025-04-15HEBEI GELLEC NEW ENERGY MATERIAL SCI&TECHNOLOY CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510035840.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-09
Publication Date
2025-04-15
Estimated Expiration
2045-01-09

AI Technical Summary

Technical Problem

The existing lithium-ion battery separators have shortcomings in heat resistance, liquid absorption, liquid retention, ionic conductivity, wetting, needle puncture strength and peel strength, which affect the cycling and safety performance of the battery.

Method used

By synergistically using porous aluminum oxide, ethyleneimine, silane coupling agent and polyvinyl alcohol, a lithium battery separator with high heat resistance and high liquid absorption retention rate is prepared. The method includes mixing the above-mentioned materials in a specific proportion, forming a slurry, and drying it by coating onto the base film to form a high-performance lithium battery separator.

Benefits of technology

The liquid absorption rate, liquid retention rate, ionic conductivity, needle puncture strength, peel strength and heat resistance of the lithium battery separator are significantly improved, and the overall performance and safety performance of the battery are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119833877A_ABST
    Figure CN119833877A_ABST
Patent Text Reader

Abstract

The invention discloses a lithium battery diaphragm with high heat resistance and high liquid absorption and retention rate and a preparation method thereof, and the method for preparing slurry comprises the following steps: uniformly mixing porous alumina, first water, an ethyleneimine aqueous solution, a silane coupling agent solution, a polyvinyl alcohol aqueous solution, a dispersant and a binder to obtain the slurry. And coating a base membrane with the slurry, and drying to obtain a coating on the base membrane, thereby obtaining the lithium battery diaphragm with high heat resistance and high liquid absorption and retention rate. The lithium battery diaphragm with high heat resistance and high liquid absorption and retention rate has good liquid absorption rate, liquid retention rate, ionic conductivity, needling strength and peel strength, and good heat resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of battery separators, and in particular relates to a lithium battery separator with high heat resistance and high liquid absorption and retention rate and a preparation method thereof. Background Art

[0002] Lithium-ion batteries are a very popular technology in the field of electronic devices, mainly because they have higher energy density and longer cycle life. In lithium-ion batteries, the function of the battery separator is to serve as an isolation medium between the positive and negative electrodes to promote the movement of lithium ions. At present, most commercial lithium-ion battery separators use polyolefin separators, such as polyethylene film and polypropylene film. Polyolefin separators lack polar and hydrophilic groups, resulting in poor hydrophilicity and ionic conductivity of the battery separator. The micropores on the surface of the battery separator are usually formed by a stretching process, which has poor heat resistance and electrolyte wettability. This is not conducive to the cycle performance and safety performance of the battery. At this stage, the surface morphology and structure of the separator can be modified by coating or grafting to improve the thermal stability of the separator, improve the separator's resistance to heat shrinkage, mechanical strength, ionic conductivity and wettability, thereby improving the overall performance of the battery. However, the modification of existing technologies still cannot fully meet the application requirements of lithium-ion batteries. Summary of the invention

[0003] In view of the shortcomings of the prior art, an object of the present invention is to provide a method for preparing slurry.

[0004] Another object of the present invention is to provide a slurry obtained by the above method.

[0005] Another object of the present invention is to provide a lithium battery separator with high heat resistance and high liquid absorption and retention rate.

[0006] The purpose of the present invention is achieved through the following technical solutions.

[0007] A method for preparing a slurry comprises: mixing porous alumina, first water, an ethyleneimine aqueous solution, a silane coupling agent solution, a polyvinyl alcohol (PVA) aqueous solution, a dispersant and a binder until uniformly mixed to obtain a slurry, wherein the ratio of the porous alumina, the first water, the ethyleneimine aqueous solution, the silane coupling agent solution, the polyvinyl alcohol aqueous solution, the dispersant and the binder is (20-30): (50-60): (1-5): (0.5-2): (1-5): (0.2-0.5): (5-10) by mass.

[0008] In the above technical solution, the ratio of the porous alumina, the first water, the ethyleneimine aqueous solution, the silane coupling agent solution, the polyvinyl alcohol aqueous solution, the dispersant and the binder is preferably (20-30): (50-60): (1-3): (0.5-1.5): (3-5): (0.2-0.5): (6-10) in parts by mass.

[0009] In the above technical solution, the ratio of the porous alumina, the first water, the ethyleneimine aqueous solution, the silane coupling agent solution, the polyvinyl alcohol aqueous solution, the dispersant and the binder is more preferably (20-30): (50-60): (1.5-2.5): (0.5-1.5): (3-4): (0.2-0.5): (6-10) in parts by mass.

[0010] In the above technical solution, the content of ethyleneimine in the ethyleneimine aqueous solution is 5 to 15 wt%.

[0011] In the above technical solution, the content of the silane coupling agent in the silane coupling agent solution is 1 to 10 wt %.

[0012] In the above technical solution, the content of polyvinyl alcohol in the polyvinyl alcohol aqueous solution is 5 to 15 wt %.

[0013] In the above technical solution, the binder is an acrylate copolymer solution, and the content of the acrylate copolymer in the acrylate copolymer solution is 20-40wt%.

[0014] In the above technical solution, the dispersant is ammonium polyacrylate.

[0015] In the above technical solution, the silane coupling agent is at least one of γ-glycidyloxypropyltrimethoxysilane (KH560) and γ-aminopropyltriethoxysilane (KH550).

[0016] In the above technical solution, the particle size of the slurry is D50=0.25-0.5 microns, and D90=0.8-1.2 microns.

[0017] The method for preparing the above slurry specifically comprises the following steps:

[0018] Step 1, mixing first water, a silane coupling agent solution and a dispersant until uniform to obtain a first solution;

[0019] In step 1, the first water, the silane coupling agent solution and the dispersant are mixed and stirred until uniform. The stirring speed is 500 to 1500 r / min, the revolution speed is 30 to 50 r / min, and the stirring time is 10 to 20 minutes.

[0020] Step 2, mixing the first solution, the ethyleneimine aqueous solution and the porous alumina until uniform, to obtain a second solution;

[0021] In step 2, the first solution, the ethyleneimine aqueous solution and the porous alumina are mixed and stirred until uniform. The stirring speed is 1500-2500 r / min, the revolution speed is 30-50 r / min, and the stirring time is 20-30 minutes.

[0022] Step 3: Mix the second solution, the binder and the polyvinyl alcohol aqueous solution until they are uniform to obtain a slurry.

[0023] In step 3, the second solution, the binder and the polyvinyl alcohol aqueous solution are mixed, and ultrasonically and stirred simultaneously for 15 to 25 minutes in a vacuum environment until they are uniform, wherein the vacuum degree of the vacuum environment is 500 to 1500 Pa. The rotation speed of the stirring is 1000 to 2500 r / min, the revolution speed is 30 to 50 r / min, and the ultrasonic frequency of the ultrasonic wave is 5 to 10 kHz.

[0024] The slurry obtained by the above method.

[0025] A method for preparing a high-heat-resistant and high-liquid-absorption-and-retention-rate lithium battery diaphragm comprises: coating the slurry on a base film, drying, obtaining a coating on the base film, and obtaining a high-heat-resistant and high-liquid-absorption-and-retention-rate lithium battery diaphragm.

[0026] In the above technical solution, the base film is a hydrophilic film, and the water contact angle of the base film is 20 to 50°, preferably 20 to 30°.

[0027] In the above technical scheme, the method for obtaining the hydrophilic film includes: immersing the PE film in a first mixed liquid at room temperature for 30 to 40 minutes, washing, and drying to obtain a hydrophilic film, wherein the first mixed liquid includes: ethanol, water and lithium citrate, and the ratio of the volume fraction of ethanol, the volume fraction of water in the first mixed liquid and the mass fraction of lithium citrate is (50 to 60): (20 to 30): 20, the unit of mass fraction is g, and the unit of volume fraction is mL.

[0028] In the above technical solution, lithium citrate is introduced through a hydrated lithium citrate solution, and the content of lithium citrate in the hydrated lithium citrate solution is 5-10wt%.

[0029] In the above technical solution, the coating speed is 20-40 m / min.

[0030] In the above technical solution, the thickness of the coating is 2 to 3 μm.

[0031] Application of porous alumina, ethyleneimine, silane coupling agent and polyvinyl alcohol to synergistically improve the liquid absorption rate and / or liquid retention rate of the diaphragm.

[0032] Application of porous alumina, ethyleneimine, silane coupling agent and polyvinyl alcohol to synergistically improve the ionic conductivity of the separator.

[0033] Application of porous alumina, ethyleneimine, silane coupling agent and polyvinyl alcohol to synergistically improve the wettability of the membrane.

[0034] Application of porous alumina, ethyleneimine, silane coupling agent and polyvinyl alcohol to synergistically improve the needle puncture strength and / or peel strength of the separator.

[0035] Application of porous alumina, ethyleneimine, silane coupling agent and polyvinyl alcohol to synergistically improve the heat resistance of the diaphragm.

[0036] Application of porous alumina, ethyleneimine, silane coupling agent and polyvinyl alcohol to synergistically reduce interface resistance.

[0037] Compared with the prior art, the present invention has the following beneficial effects:

[0038] Porous alumina, ethyleneimine, silane coupling agent and polyvinyl alcohol synergistically improve the liquid absorption rate, liquid retention rate, ionic conductivity, needle puncture strength, peel strength and heat resistance of the separator.

[0039] 1. Ethylenimine has a certain flexibility. The synergistic effect of ethyleneimine and porous alumina makes the coating have better flexibility while maintaining a certain mechanical strength. The amine group of ethyleneimine can react with the hydroxyl group on the surface of porous alumina to form hydrogen bonds, enhance the polarity and hydrophilicity of the coating surface, help reduce the contact angle of the liquid on the coating surface, enable the liquid to contact the coating more fully, and improve the coating's ability to adsorb and retain liquids.

[0040] 2. Ethylenimine interacts with the active groups (hydroxyl, carboxyl) on the surface of the hydrophilic membrane through the amine group to form hydrogen bonds, thereby improving the adhesion of the coating to the base membrane. Porous alumina fills the surface pores of the diaphragm, increasing the contact area between the coating and the base membrane, further improving the adhesion.

[0041] 3. The citrate ion in the hydrated lithium citrate solution is a group with a certain hydrophilicity. Using the hydrated lithium citrate solution to treat the PE membrane can reduce the surface tension of the PE membrane, making it easier for the electrolyte to spread and penetrate on the surface of the PE membrane, and the hydrophilicity of the diaphragm is significantly improved.

[0042] 4. The chemical bonds in lithium citrate can absorb some heat at high temperatures, which can prevent the diaphragm from shrinking or melting excessively at high temperatures. In addition, porous alumina and ethyleneimine have high thermal stability, can maintain good structural stability in high temperature environments, and effectively resist the damage to the diaphragm caused by thermal stress. The interface impedance between the diaphragm and the electrode is also significantly reduced. This is because there are a large number of polar groups (hydroxyl and amine groups) on the surface of the high heat-resistant and high liquid absorption and retention lithium battery diaphragm. These polar groups enhance the polarity of the diaphragm surface, making the migration process of ions in the diaphragm easier, thereby effectively reducing the impedance related to ion migration. This comprehensive performance improvement provides a strong guarantee for the high-performance operation of lithium batteries, and provides new ideas and methods for the development of lithium batteries in terms of high energy density and high safety. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1 The contact angle of the lithium battery separator prepared in Comparative Example 3;

[0044] Figure 2 The contact angle of the high heat-resistant and high liquid absorption and retention rate lithium battery separator prepared in Example 8;

[0045] Figure 3 This is a SEM of the high heat-resistant and high liquid absorption and retention rate lithium battery separator prepared from the slurry of Example 2. DETAILED DESCRIPTION

[0046] The technical solution of the present invention is further described below in conjunction with specific embodiments.

[0047] Porous alumina: Shanghai Yingcheng New Materials Co., Ltd.;

[0048] Polyvinyl alcohol aqueous solution: Guangzhou Xiangqian Chemical Co., Ltd.;

[0049] Acrylate copolymer (acrylate and vinylidene fluoride) solution: Ningbo Xinfei Plastic Chemical Co., Ltd.;

[0050] Ammonium polyacrylate: Shanghai Sanrui Polymer Materials Technology Co., Ltd.;

[0051] Hydrated lithium citrate solution: Hubei Watson Chemical Technology Co., Ltd.;

[0052] Silane coupling agent solution: Shandong Jinyufeng New Materials Co., Ltd.

[0053]

[0054] Double planetary mixer: XFZH-30L.

[0055] In the following embodiments and comparative examples, the method for preparing a hydrophilic film is as follows: immersing a PE film in a first mixed solution at room temperature for 30 minutes, washing (rinsing with deionized water three times), and drying at 75°C for 20 minutes to obtain a hydrophilic film (water contact angle is 24.6°), wherein the method for obtaining the first mixed solution is as follows: adding ethanol and deionized water to a beaker and stirring at room temperature, the stirring speed is 1000r / min, the stirring time is 10min, and then adding a hydrated lithium citrate solution (the content of lithium citrate in the hydrated lithium citrate solution is 5wt%), stirring at a speed of 1000r / min for 30 minutes at 40°C until it is clarified to obtain a first mixed solution. In the first mixed solution, the ratio of the volume fraction of ethanol, the volume fraction of water and the mass fraction of lithium citrate is 50:30:20, the unit of mass fraction is g, and the unit of volume fraction is mL.

[0056] Ionic conductivity: The test temperature is 25°C and the relative humidity is 50%.

[0057] Peel strength: prepare a sample of standard size (width 10-25mm, length 150mm), use 3M transparent tape to stick it on the coating surface of the sample, and leave enough peeling end (at least 20mm), use a standard roller to press the sample evenly 3 times, fix the two ends of the sample in the upper and lower clamps respectively, with the peeling direction of 180°, use a stretching machine to tear off one end of the 3M transparent tape to obtain the peel strength.

[0058] The electrolyte used in the contact angle test is a mixture of electrolyte and solvent, the electrolyte is LiPF6, the electrolyte concentration is 1M, the solvent is a mixture of ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate, and the volume ratio of ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate is 1:1:1.

[0059] Examples 1 to 3

[0060] A method for preparing a slurry comprises the following steps:

[0061] Step 1, mixing the first water (pure water), the silane coupling agent solution and the dispersant in a double planetary mixer, stirring until uniform (stirring rotation speed is 1000r / min, revolution speed is 40r / min, stirring time is 10 minutes), to obtain a first solution, the dispersant is ammonium polyacrylate, the content of the silane coupling agent in the silane coupling agent solution is 5wt%, and the silane coupling agent is γ-glycidyloxypropyltrimethoxysilane (KH560);

[0062] Step 2, adding an ethyleneimine aqueous solution and porous alumina (powder) to the first solution, stirring until uniform (stirring rotation speed is 2000r / min, revolution speed is 40r / min, stirring time is 30 minutes), to obtain a second solution, the content of ethyleneimine in the ethyleneimine aqueous solution is 10wt%;

[0063] Step 3, add a binder and a polyvinyl alcohol aqueous solution to the second solution, in a double planetary mixer with a high-speed dispersed ultrasonic oscillation function, ultrasonic and stir for 20 minutes in a vacuum environment until uniform, to obtain a slurry, wherein the vacuum degree of the vacuum environment is 1000pa. The stirring rotation speed is 2000r / min, the revolution speed is 40r / min, the ultrasonic frequency of the ultrasound is 5kHz, the binder is an acrylate copolymer solution, the content of the acrylate copolymer in the acrylate copolymer solution is 30wt% (the acrylate copolymer is polymerized by acrylate and vinylidene fluoride), the content of polyvinyl alcohol in the polyvinyl alcohol aqueous solution is 10wt%, and the ratio of porous alumina, the first water, the ethyleneimine aqueous solution, the silane coupling agent solution, the polyvinyl alcohol aqueous solution, the dispersant and the binder is X by mass.

[0064] The X values ​​are shown in Table 1.

[0065] Table 1

[0066] Slurry X Example 1 25:60:1:1:4.5:0.5:8 Example 2 25:60:2:1:3.5:0.5:8 Example 3 25:60:5:2:2.5:0.5:5

[0067] The particle size of the slurry prepared in Example 1 is D50: 0.454 microns, D90: 1.035 microns; the particle size of the slurry prepared in Example 2 is D50: 0.420 microns, D90: 1.055 microns; the particle size of the slurry prepared in Example 3 is D50: 0.454 microns, D90: 1.103 microns.

[0068] Example 4

[0069] A method for preparing slurry is basically the same as that of Example 1, except that no silane coupling agent solution is added in the method for preparing slurry in Example 4.

[0070] Example 5

[0071] A method for preparing slurry is basically the same as that of Example 1, except that no ethyleneimine aqueous solution is added in the method for preparing slurry in Example 5.

[0072] Example 6

[0073] A method for preparing slurry is basically the same as that of Example 1, except that no polyvinyl alcohol aqueous solution is added in the method for preparing slurry in Example 6.

[0074] Comparative Example 1

[0075] A method for preparing a slurry comprises the following steps:

[0076] Step 1, pure water and dispersant are placed in a double planetary mixer and mixed, and stirred for 10 minutes at a rotation speed of 1000 r / min and a revolution speed of 40 r / min to obtain solution A;

[0077] Step 2, adding porous alumina (powder) to solution A, stirring at a rotation speed of 2000 r / min and a revolution speed of 40 r / min for 30 minutes to obtain solution B;

[0078] Step 3, adding a binder to solution B, and simultaneously ultrasonicating and stirring for 20 minutes in a double planetary mixer with a high-speed dispersing ultrasonic oscillation function under a vacuum environment until the mixture is uniform, to obtain a slurry, wherein the stirring rotation speed is 2000 r / min, the revolution speed is 40 r / min, the ultrasonic frequency is 5 kHz, and the vacuum degree is 1000 Pa;

[0079] The ratio of porous alumina, pure water, dispersant and binder is 35:60:0.5:9.5 by mass. The dispersant and binder in Comparative Example 1 are the same as those in Example 1.

[0080] The particle sizes of the slurry prepared in Comparative Example 1 are D50: 0.441 μm, D90: 1.054 μm.

[0081] Comparative Example 2

[0082] A method for preparing a slurry is basically the same as that of Comparative Example 1, except that the "porous alumina" is replaced by "conventional alumina", the particle sizes of the conventional alumina are: D10: 0.336 μm, D50: 0.537 μm, D90: 1.079 μm, and the specific surface area is 11.5 m 2 / g, pore size is 9.1nm.

[0083] The particle sizes of the slurry prepared in Comparative Example 2 are D50: 0.487 microns and D90: 1.335 microns.

[0084] Embodiments 7 to 12

[0085] A method for preparing a high heat-resistant and high liquid absorption and retention lithium battery separator comprises: placing a base film on a coating machine, coating the base film with a slurry on one side at a speed of 30 m / min, entering a drying device under the traction of a traction roller, drying at 50° C. for 10 minutes, obtaining a coating on the base film, and obtaining a high heat-resistant and high liquid absorption and retention lithium battery separator. The base film is a hydrophilic film, and the slurry is one of Examples 1 to 6.

[0086] Table 2

[0087] High heat resistance and high liquid absorption and retention rate lithium battery diaphragm Slurry for preparing lithium battery diaphragm with high heat resistance and high liquid absorption and retention rate Example 7 Example 1 Example 8 Example 2 Example 9 Example 3 Example 10 Example 4 Embodiment 11 Example 5 Example 12 Example 6

[0088] Comparative Examples 3-4

[0089] A method for preparing a lithium battery separator comprises: placing a base film on a coating machine, coating the base film with a slurry on one side at a speed of 30 m / min, entering a drying device under the traction of a traction roller, drying at 50° C. for 10 minutes, obtaining a coating on the base film, and obtaining a lithium battery separator. The base film is a PE film (non-hydrophilic film), and the slurry is one of the comparative examples 1 to 2.

[0090] Table 3

[0091] Lithium battery diaphragm Slurry for preparing lithium battery diaphragm Comparative Example 3 Comparative Example 1 Comparative Example 4 Comparative Example 2

[0092] Comparative Example 5

[0093] A method for preparing a lithium battery separator is basically the same as that of comparative example 4, except that the base film used in comparative example 5 is a hydrophilic film.

[0094] The parameters of the high heat-resistant and high liquid absorption and retention rate lithium battery separator (Example 7) prepared from the slurry of Example 1 are as follows:

[0095]

[0096] The parameters of the high heat-resistant and high liquid absorption and retention rate lithium battery separator (Example 8) prepared from the slurry of Example 2 are as follows:

[0097]

[0098]

[0099] The parameters of the high heat-resistant and high liquid absorption and retention rate lithium battery separator (Example 9) prepared from the slurry of Example 3 are as follows:

[0100]

[0101] The parameters of the high heat-resistant and high liquid absorption and retention rate lithium battery separator (Example 10) prepared from the slurry of Example 4 are as follows:

[0102]

[0103]

[0104] The parameters of the high heat-resistant and high liquid absorption and retention rate lithium battery separator (Example 11) prepared from the slurry of Example 5 are as follows:

[0105]

[0106] The parameters of the high heat-resistant and high liquid absorption and retention rate lithium battery separator (Example 12) prepared from the slurry of Example 6 are as follows:

[0107]

[0108] The parameters of the lithium battery separator (Comparative Example 3) prepared from the slurry of Comparative Example 1 are as follows:

[0109]

[0110] The parameters of the lithium battery separator (Comparative Example 4) prepared from the slurry of Comparative Example 2 are as follows:

[0111]

[0112] The parameters of the lithium battery separator (Comparative Example 5) prepared from the slurry of Comparative Example 2 are as follows:

[0113]

[0114] Silane coupling agent can react with the hydroxyl groups on the surface of porous alumina to form silanol (-Si-OH), and then further form covalent bonds (-Si-O-Al), thereby chemically modifying the surface of alumina. Through the modification of silane coupling agent, active epoxy groups are introduced into the surface of porous alumina, which provides chemical reaction sites for subsequent combination with ethyleneimine. Silane coupling agent establishes a chemical connection between porous alumina and ethyleneimine. The epoxy groups introduced by silane coupling agent undergo ring-opening reaction in ethyleneimine aqueous solution, forming stable amide bonds with abundant primary amine groups on the surface of ethyleneimine, thereby combining porous alumina with ethyleneimine (porous alumina is successfully grafted onto the macromolecular chain of ethyleneimine). Then, polyvinyl alcohol (PVA) aqueous solution is added, and the hydroxyl groups in PVA can combine with the active groups on the surface of the hydrophilic membrane to form hydrogen bonds, thereby firmly attaching the coating to the base membrane.

[0115] like Figure 1 and Figure 2 As shown, the contact angle of the lithium battery separator prepared in Comparative Example 3 is 15.136°, and the contact angle of the high heat-resistant and high liquid absorption and retention rate lithium battery separator prepared in Example 8 is 4.35°, indicating that the wettability of the modified porous alumina is relatively excellent. Figure 3 This is a SEM of the high heat-resistant and high liquid absorption and retention rate lithium battery separator prepared from the slurry of Example 2.

[0116] Ceramic (porous alumina) particles are attached to the surface of the base film, which can store a large amount of electrolyte and is conducive to the absorption of electrolyte by the diaphragm. In addition, there are a large number of hydrophilic hydroxyl (-OH) polar groups on the surface of porous alumina, which is conducive to improving the wettability of the diaphragm to the electrolyte. The present invention improves the heat resistance, wettability and ion conductivity of the diaphragm through the synergistic effect of ethyleneimine, porous alumina, silane coupling agent and polyvinyl alcohol, thereby improving the overall performance of the battery.

[0117] The present invention is described above by way of example. It should be noted that, without departing from the core of the present invention, any simple deformation, modification or other equivalent replacement that can be made by those skilled in the art without inventive effort falls within the protection scope of the present invention.

Claims

1. A method for preparing a slurry, characterized in that: include: The porous alumina, the first water, the ethyleneimine aqueous solution, the silane coupling agent solution, the polyvinyl alcohol aqueous solution, the dispersant and the binder are mixed until uniform to obtain a slurry. The ratio of the porous alumina, the first water, the ethyleneimine aqueous solution, the silane coupling agent solution, the polyvinyl alcohol aqueous solution, the dispersant and the binder is (20-30): (50-60): (1-5): (0.5-2): (1-5): (0.2-0.5): (5-10) by mass.

2. The method according to claim 1, characterized in that The silane coupling agent is at least one of γ-glycidyloxypropyltrimethoxysilane and γ-aminopropyltriethoxysilane.

3. The method according to claim 1, characterized in that The content of ethyleneimine in the ethyleneimine aqueous solution is 5-15wt%; the content of silane coupling agent in the silane coupling agent solution is 1-10wt%; the content of polyvinyl alcohol in the polyvinyl alcohol aqueous solution is 5-15wt%; the binder is an acrylate copolymer solution, and the content of acrylate copolymer in the acrylate copolymer solution is 20-40wt%.

4. The slurry obtained by the method according to any one of claims 1 to 3.

5. A method for preparing a lithium battery separator with high heat resistance and high liquid absorption and retention rate, characterized in that: include: The slurry described in claim 4 is coated on a base film and dried to obtain a coating on the base film, thereby obtaining a lithium battery separator with high heat resistance and high liquid absorption and retention rate.

6. The preparation method according to claim 5, characterized in that: The base film is a hydrophilic film, and the water contact angle of the base film is 20 to 50 degrees.

7. Application of porous alumina, ethyleneimine, silane coupling agent and polyvinyl alcohol to synergistically improve the liquid absorption rate and / or liquid retention rate of the diaphragm.

8. Application of porous alumina, ethyleneimine, silane coupling agent and polyvinyl alcohol to synergistically improve the ionic conductivity of the membrane.

9. Application of porous alumina, ethyleneimine, silane coupling agent and polyvinyl alcohol to synergistically improve the wettability and / or heat resistance of the membrane.

10. Application of porous alumina, ethyleneimine, silane coupling agent and polyvinyl alcohol to synergistically improve the needle puncture strength and / or peel strength of the separator.

Citation Information

Patent Citations

  • Lithium battery diaphragm as well as preparation method and application thereof

    CN119253188A

  • Separator for electrochemical device and electrochemical device using the same

    JP2016062849A

  • Ceramic coated separator having excellent thermal property and electro-chemical stability and the manufacturing method of it

    KR1020150084116A

  • Separator for rechargeable lithium battery and rechargeable lithium battery including the same

    US20200287191A1

  • NANO slurry and preparation method therefor, battery separator and manufacturing method therefor, and battery

    WO2023155191A1